Analysis of Association between Obesity and Musculoskeletal System Outcomes in Children and Adolescents: An Institutional Based Study - Verma, Puneet; Bhadani, Yogesh Hareshbhai (Asian Journal of Medical Research, 2018)
Background: The identification of an elevated fracture risk in obese children has prompted an examination of the interplay between adipose tissue, bone health, and the effects of obesity on skeletal maturation. Hence, the present study was conducted to analyze association between obesity and musculoskeletal system outcomes in children and adolescents. Materials & Methods: A total of 50 obese children (study group) and 50 non-obese healthy children (Control group) were enrolled. Complete demographic and clinical details of all the patients were obtained. All participants in the study were aged between 8 and 16 years. Arthrometric measurements for each subject were documented. A comprehensive assessment of the musculoskeletal system was conducted, incorporating various screening techniques for musculoskeletal disorders in children. This assessment included evaluations of range of motion (ROM), the timed up and go test (TUG), and the standing time on one leg (STOOL) tests. Data analysis was carried out using SPSS software, employing the Chi-square test and Student’s t-test to determine the significance levels. Results: Mean age of the subjects of the study group and control group was 12.3 years and 11.7 years respectively. There were 31 males and 19 females in the study group while there were 28 males and 22 females in the control group. Significantly better results of STOLL test and TUG test were seen among control group. Also, while comparing the range of motion among the non-obese and obese groups, subjects of the non-obese group showed better shoulder flexion, elbow flexion, wrist flexion, knee flexion and foot flexion. Conclusion: Obesity and overweight represent significant global health challenges that particularly impact children and adolescents. Excess weight during these formative years can profoundly affect the health and overall well-being of young individuals, potentially leading to chronic health issues such as musculoskeletal pain and dysfunction of bones and joints in adulthood.